Men in black - Smith, Will; Sony Music Entertainment (New York : Sony Music Entertainment, 1997)
Contains tracks from the soundtrack of Men In Black plus a bonus track.
CD 1 : Men In Black / (3:48) -- Track Masters Instrumental / (3:48) -- Track Masters A Cappella / (3:29) -- Some Cow Fonque (More Tea, Vicar?) / (5:10).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Film soundtracks; Motion picture music